Rubric to assess presentations of clinical cases: instrument that orients the quality in performance - Urias Barreras, Cynthia Marina; Rodríguez, Carlota Leticia; Zárate Depraect, Nikell Esmeralda (Acta Universitaria, 2019)
The Faculty of Dentistry of the Autonomous University of Sinaloa (UAS, for its acronym in Spanish) implements an educational model based on integrated professional competencies, which involves a performance assessment based on criteria of quality, feedback, diversification of actors and moments, with related evaluation instruments. An investigation of quantitative approach, pre-experimental design, case study-like, of descriptive scope was carried out in order to test the Rubric to evaluate presentations of clinical cases as an instrument that guides quality in performance, from the co-evaluation and hetero-evaluation; comparisons were made per shift and gender. As a result, better grades were obtained when evaluating performance in the morning shift and in the female gender (hetero-evaluation), as well as in the evening shift and female gender (co-evaluation). The "Rubric to evaluate presentations of clinical cases" is a valid instrument to guide the quality in the performance of the students through the co-evaluation and hetero-evaluation.
Keywords: Array; Array; Array; Array; Array